PENGARUH COVID-19 TERHADAP PEREKONOMIAN MASYARAKAT DI DISTRIK KLAMONO KABUPATEN SORONG - Arce Yulita Ferdinandus; Ratna Pakpahan; Jeklin Mlaskit (BADATI, 2022)
The emergence of the Covid-19 outbreak had a significant impact on the economy of the Klamono district community, many people complained that the cessation of activities resulted in weak household consumption and also weak public purchasing power due to the corona disease making it difficult for people to earn income because the majority of the people were selling. What is experienced by the people of the Klamono district in this problem is that the community's economy has decreased drastically, people's income has decreased. The purpose of this study was to determine the effect of covid-19 on the economy of the community in the Klamono district, Sorong district. To find out the impact of covid-19 on the economy of the community in the Klamono district, Sorong district. This research method is descriptive qualitative. From the results of hypothesis testing that has been done the hypothesis is accepted. The results obtained are based on calculations, the R² value is 0.177 or 17.7%. This shows that the percentage of the impact of covid 19 on the community's economy is 17.7%. In other words, the people's economy chooses to be explained or influenced by the covid 19 variable by 17.7% while the remaining 83.3% is explained or influenced by other variables not examined. The results of the t-count value of the customer value variable can be seen that the t-count value is 4.519 which is greater than the t-table value of 1.6611. Thus the hypothesis is accepted, meaning that the Covid 19 variable has a significant influence on the community's economy.